Struggle for recognition, rights, and redistribution: Understanding the identity of parents of children with autism spectrum disorder in China - Liu, Ying; Fisher, Karen R. (Frontiers in Psychology, 2023)
The number of children diagnosed with autism spectrum disorders (ASD) worldwide has increased rapidly in the past decade and China is no exception. Yet the identity development of Chinese parents of children with ASD is little understood. This study employed an ethics of care perspective to explore the identity of parents of children with ASD as shaped in their social cultural context in mainland China. Qualitatively-driven mixed-method design was adopted. Qualitative data about their experiences were obtained from in-depth interviews with 20 parents from 17 families of children with ASD in Beijing and participant observation of 9 participants’ daily parenting experience. A complex and dynamic parenting identity was revealed. With limited recognition within and external to the family, parents experienced constant challenges towards their sense of self. The parents used strategies to assert their rights as carers and develop positive self-perceptions. Yet because of the unjust distribution of care work within families and with the state, the parents retained a sense of insecurity throughout the process of parenting. The parents’ sense of inferiority due to devaluing children with disabilities was accentuated by traditional Chinese cultural values about good parenting. They were intensely worried about the lack of policy for support as they and their children grew older. The findings reinforce the need for recognition of parents’ dignity, capacity and efforts in caring.